TREN PERUBAHAN PENGGUNAAN LAHAN DI LAHAN PERTANIAN KOTA DI KECAMATAN KASIHAN KABUPATEN BANTUL - Wiwaha, Adam Abraham; Pramono, Retno Widodo D (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2020)
For more than decade, agriculutre lands in the Kasihan Subdistrict were affected by the development of Yogyakarta City. Those trends are mainly caused by their location which are directly facing thecity and the function of Kasihan Subdistrict as a Yogyakarta Urban Area (Kawasan Perkotaan Yogyakarta). Besides, the farmers of Kasihan Subdistrict are in their old age, making them more vulnerable to the landuse change it self. Hence it is important to understand the trend of the landuse changeand its impact to the agriculture land in the Kasihan Subdistrict.This research used deductive approach which its variables are formulated from the recent studies. In addition,overlay analysis was used for the landsat and bingmap multi temporal imagery data. The results of the overlay then were being compared to the social economic data of the Kasihan Subdistrict such as gross domestic regional bruto, farmer data, local borderline map, and any relevant data for further analysis.The results of the analysis show that landuse change grow faster in the rural area rather than in the cities. Bangunjiwo village are the most affected to the changes even tough in spacial zoning regulation, it isn't stated as an urban area. As the changes took place in productive land, local government need to make an affirmative program for the farmers so that the farmers have reasons and motivation to continue their farming within the city. Such programs will prevent the landuse changes to grow wide